Magnetic Nanofiber Layers as a Functional Surface for Biomolecule Immobilization and One‐Use 'Sensing in‐a‐Drop' Applications. Issue 48 (21st December 2018) - Sanli, Serdar; Celik, Emine Guler; Demir, Bilal; Gumus, Z. Pinar; Ilktac, Raif; Aksuner, Nur; Demirkol, Dilek Odaci; Timur, Suna
Abstract: Stabilization of biomolecules on matrices is critically important. Here we constructed composite nanofibers with magnetic features by electro‐spinning of magnetic nanoparticles (MNP) in an appropriate polymer matrix on a collector surface for multiple uses. 'Poly(vinylalcohol)‐polyethyleneimine/Fe3 O4 magnetic nanoparticles' (PVA‐PEI/MNP) composite nanofiber was used on the screen printed electrodes (SPE) to serve as a platform for the glucose oxidase (GOx) biofilm as the model biomolecule. To show the potential application of this material as a biosensor component, the resulted biofilm, called 'PVA‐PEI/MNP/GOx', was fixed on SPE via a neodymium magnet for the electrochemical detection of glucose at −0.7 V where oxygen consumption due to enzymatic reaction was measured. The main advantage of the obtained magnetic biomembrane is that it allows analysis with a single drop. After step‐by‐step surface modifications, analytical characterization was performed using various techniques, such as voltammetry, electrochemical impedance spectroscopy, Fourier‐transform infrared spectroscopy and X‐Ray photoelectron spectroscopy as well as microscopic techniques. The linear range of the PVA‐PEI/MNP/GOx surface was found as 0.0125 to 0.5 mM with a limit of detection of 11.5 μM for glucose as analyte. The application of PVA‐PEI/MNP/GOx for glucose detection in synthetic samples was carried out. Data proved the potential use of the 'PVA‐PEI/MNP' surface as a biomolecule immobilization platform for disposable biosensor applications. Abstract : 'Poly(vinylalcohol)‐polyethyleneimine/Fe3 O4 magnetic nanoparticles' (PVA‐PEI/MNP) composite nanofiber was used on the screen printed electrodes (SPE) to serve as a platform for the glucose oxidase (GOx) biofilm as the model biomolecule. The main advantage of the obtained magnetic biomembrane is that it allows analysis with a single drop. Data proved the potential use of the 'PVA‐PEI/MNP' surface as a biomolecule immobilization platform for disposable biosensor applications.